Using Hybrid Modeling for Estimation of the Efficiency of Service Systems - Oo, Tun Min; Lupin, Sergey; Khaing, Min Thu; Thu, Aung (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2021)
Ensuring the efficiency of public transport is one of the most important problems for residents of megacities. There are many analytical methods for solving this problem, but their application in practice does not have a significant effect since they do not take into account the current road situation. When applied to the task of planning the operation of public transport, this means that it is considered in stationary conditions. Currently, simulation provides an analysis of the operation of complex systems and allows finding optimal solutions to the management problem, taking into account the variability of external factors. This factor is the current road traffic. The proposed hybrid model in the AnyLogic environment allows us to use GIS maps for estimating the efficiency of transport systems.